Braided geographies: bordered forms and cross-border formations in refugee comics. Issue 2 (3rd April 2019) - Davies, Dominic
ABSTRACT: This article offers a close analysis of a trilogy of 'refugee comics' entitled 'A Perilous Journey', which were produced in 2015 by the non-profit organisation PositiveNegatives, to conceive of comics as a bordered form able to establish alternative cross-border formations, or 'counter-geographies', as it calls them. Drawing on the work of Martina Tazzioloi, Thierry Groensteen, Jason Dittmer, Michael Rothberg and others, the article argues that it is by building braided, multi-directional relationships between different geographic spaces, both past and present, that refugee comics realise a set of counter-geographic and potentially decolonising imaginaries. Through their spatial form, refugee comics disassemble geographic space to reveal counter-geographies of multiple synchronic and diachronic relations and coformations, as these occur between different regions and locations, and as they accumulate through complex aggregations of traumatic and other affective memories. The article contends that we need an interdisciplinary combination of the critical reading skills of humanities scholars and the rigorous anthropological, sociological and theoretical work of the social sciences to make sense of the visualisation of these counter-geographic movements in comics. It concludes by showing how the counter-geographies visualised by refugee comics can subvert the geopolitical landscape of discrete nation-states and their territorially bound imagined communities.